The Ratio of Storage Volume to Cubic Number for Rampus Nets at The Karangantu Archipelago Fishery Port-Banten - Annisa Ramadhanti; Yopi Novita; Mohammad Imron; Tri Nanda Citra Bangun; Budhi Hascaryo Iskandar (Universitas Gadjah Mada, 2022)
The Banten Province Maritime Affairs and Fisheries Service plans to standardize the hold volume for fishing vessels in its management area. The management plan is still challenging to implement because there is no information about the vessel storage volume. In addition, small fishing vessel fishers still store their catch in boxes made of fibre-reinforced plastic (FRP). That box is often placed on the deck floor, causing decreased vessel stability. The size of the available storage volume on the vessel must be ideal, so it needs to be compared with the cubic number. This research aims to determine the optimal storage volume to cubic number ratio for rampus net vessels with the best stability conditions. The sampling technique used was accidental sampling with a total sample of 10% from 72 fishing vessels. Data processing used mathematical calculations and stability simulation with the GZ program. Analysis of the data used is descriptive analysis. The results showed that the optimal ratio of storage volume to cubic number for vessels with sizes 3-5 GT ranged from 5.03 - 8.55%. That ratio was a storage condition designed inside the hull construction, and the catch is directly put into the store without using the FRP box. From the stability point of view, condition 3 is the best for the quality of fishing vessel’s stability. This due to the lowest value of KG in condition 3 comparing to other conditions.